Urbanism and empire in Roman Sicily - Pfuntner, Laura (Ashley and Peter Larkin series in Greek and Roman culture., 2019)
Sicily has been the fulcrum of the Mediterranean throughout history. The island?s central geographical position and its status as ancient Rome?s first overseas province make it key to understanding the development of the Roman Empire. Yet Sicily?s crucial role in the empire has been largely overlooked by scholars of classical antiquity, apart from a small number of specialists in its archaeology and material culture. Urbanism and Empire in Roman Sicily offers the first comprehensive English-language overview of the history and archaeology of Roman Sicily since R. J. A. Wilson?s Sicily under the Roman Empire (1990). Laura Pfuntner traces the development of cities and settlement networks in Sicily in order to understand the island?s political, economic, social, and cultural role in Rome?s evolving Mediterranean hegemony. She identifies and examines three main processes traceable in the archaeological record of settlement in Roman Sicily: urban disintegration, urban adaptation, and the development of alternatives to urban settlement. By expanding the scope of research on Roman Sicily beyond the bounds of the island itself, through comparative analysis of the settlement landscapes of Greece and southern Italy, and by utilizing exciting evidence from recent excavations and surveys, Pfuntner establishes a new empirical foundation for research on Roman Sicily and demonstrates the necessity of including Sicily in broader historical and archaeological studies of the Roman Empire.